Venders’ English Speaking Ability in Tourism Object in Bali: A Survey Study - Widani, Ni Nyoman (Universitas Muhammadiyah Jember, 2019)
Bali is known as a tourist destination which is always filled with tourists, both domestic and foreigners. Besides being famous for its culture, the beach is one of the main attractions for tourists. Berawa Beach is one that is always crowded with foreign tourists because it has large waves which are great for surfing and also to enjoy the beautiful sunset. This phenomenon provides opportunities for local people as a source of income by becoming food and beverage sellers around Berawa beach. This encourages local people to use English when they transact with foreign tourists. Practically, the English language used by traders is practical English with transactional functions. This study aims to describe the ability of English use by food and beverage traders in Berawa Beach, Tibubeneng village, North Kuta District, Badung Regency in terms of the speaking aspect. In order to determine the traders speaking ability, the researcher uses scoring rubric descriptions that contain several aspects such as, grammar, pronunciation, fluency, and vocabulary. Data is collected through several instruments such as interviews, direct observation, and field notes. The results of this study can be used as input for stakeholders of Tibubeneng Village to determine the steps in improving the English language skills of food and beverage traders who ultimately can contribute positively to Badung Regency in advancing the tourism industry while introducing various kinds of local culinary.